Comparative Analysis of the Financial Performance of State-Owned Banks in Indonesia Using The RGEC Framework Before, During, and After the COVID-19 Pandemic - Puspita Rani, Ida Ayu Amara; Putra, I Nyoman Nugraha Ardana (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the financial soundness of four Indonesian state-owned banks—Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), Bank Mandiri, and Bank Tabungan Negara (BTN)—using the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) framework as regulated in POJK No. 4/POJK.03/2016, which replaced Bank Indonesia Circular Letter No. 13/24/DPNP. A longitudinal comparative approach was applied across three periods: pre-pandemic (2015–2019), pandemic (2020–2021), and post-pandemic recovery (2022–2024), based on audited annual reports and recalculated financial ratios. Results show that the pandemic negatively affected asset quality and profitability, as indicated by increased Non-Performing Loans (NPL) and reduced Return on Assets (ROA). However, Capital Adequacy Ratios (CAR) remained well above regulatory requirements, ensuring overall financial stability. Good Corporate Governance (GCG) practices also improved consistently, acting as a stabilizing factor during the crisis. By the post-pandemic period, BRI and Mandiri achieved “Very Healthy” (PK-1) ratings, while BNI and BTN maintained “Healthy” (PK-2) status. These findings highlight the importance of credit restructuring, capital strengthening, and governance quality in sustaining the resilience of state-owned banks, offering valuable insights for policymakers in enhancing Indonesia’s financial system stability.